2018
DOI: 10.1038/s41598-018-23500-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum calcium is independently associated with CKD progression

Abstract: Disturbances in calcium metabolism are common in individuals with chronic kidney disease (CKD), but whether they are associated with subsequent kidney function decline is less clear. In a CKD 3–5 cohort of 15,755 adult citizens of Stockholm with creatinine tests taken during 2006–2011 and concurrent calcium testing at cohort entry, we investigated the association between baseline serum calcium and the subsequent change in estimated glomerular filtration rate (eGFR, by CKD-EPI) decline using linear mixed models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 52 publications
4
24
0
1
Order By: Relevance
“…Our findings showing the association between hyperphosphatemia and poor renal outcome in HD patients are in line with those of previous animal researches and studies of predialysis CKD patients . Interestingly, contrary to intuition that a higher serum calcium concentration would be associated with a rapid decline in RKF, there is some evidence of the association between lower serum calcium and rapid CKD progression among nondialysis patients with CKD . However, the association between serum calcium and decline in RKF was uncertain in HD patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings showing the association between hyperphosphatemia and poor renal outcome in HD patients are in line with those of previous animal researches and studies of predialysis CKD patients . Interestingly, contrary to intuition that a higher serum calcium concentration would be associated with a rapid decline in RKF, there is some evidence of the association between lower serum calcium and rapid CKD progression among nondialysis patients with CKD . However, the association between serum calcium and decline in RKF was uncertain in HD patients.…”
Section: Discussionsupporting
confidence: 91%
“…(17,34,35) Interestingly, contrary to intuition that a higher serum calcium concentration would be associated with a rapid decline in RKF, there is some evidence of the association between lower serum calcium and rapid CKD progression among nondialysis patients with CKD. (26,27,39) However, the association between serum calcium and decline in RKF was uncertain in HD patients. In this study, we observed that lower serum calcium levels were associated with more rapid decline in RKF among incident HD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the study subjects in the present study have shown low serum Ca++. Disorders in calcium metabolism are common in patients with CKD, but whether they are associated with subsequent kidney function deterioration is unclear (Janmaat et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of the gene have been linked to gout susceptibility and to hereditary hypouricemia. Familial childhood gout with progressive renal impairment attributable to mutations of the uromodulin (UMOD) gene is associated with reduced uromodulin in the proximal tubule cilia (Janmaat et al, 2018).…”
Section: Discussionmentioning
confidence: 99%